Exploration of key markers driving ferroptosis in the progression of non-alcoholic fatty liver disease - Jiyong Zhang; Weiyan Li; Xiaoying Qiu; Yuanyuan Wang; Yongmei Zeng (PLoS ONE, 2025)
Non-alcoholic fatty liver disease (NAFLD) is a prevalent condition strongly linked to obesity, diabetes, and metabolic syndrome. Its global incidence is steadily increasing, placing a significant health burden on both patients and society. This study aims to identify ferroptosis-related differentially expressed genes (DEGs) through bioinformatics analysis and to explore their roles in NAFLD. By comparing samples from NAFLD patients and healthy controls, we identified 1,770 significant DEGs, with 1,073 being upregulated and 697 downregulated. Pathway analysis revealed a marked decrease in expression within certain key metabolic pathways (such as the one-carbon pool by folate) in the NAFLD group, while expression in DNA repair-related pathways (such as non-homologous end joining) was significantly increased. Additionally, immune cell infiltration analysis showed significant differences in 19 immune cell types between the NAFLD and control groups, with 12 types exhibiting increased infiltration in the NAFLD group. Through protein-protein interaction (PPI) network analysis, we identified 41 critical intersecting genes, and ROC curve validation demonstrated that 25 of these genes had an AUC value exceeding 0.85, highlighting their potential as biomarkers for NAFLD in early diagnosis and personalized treatment in the future.This study identifies critical ferroptosis-related genes and immune cell infiltration differences in NAFLD, offering potential biomarkers for early diagnosis and personalized treatment.